Determinants of heart failure self-care behaviour in community-based patients: a cross-sectional study - Peters-Klimm, Frank; Freund, Tobias; Kunz, Cornelia Ursula; Laux, Gunter; Frankenstein, Lutz; Müller-Tasch, Thomas; Szecsenyi, Joachim (European journal of cardiovascular nursing, 2013)
Background:Self-care behaviour in patients with heart failure (HF) represents a series of specific actions that patients should take, as an important treatment component.Aims:The aim of this study was to identify potential determinants of HF self-care in ambulatory patients with stable systolic HF.Methods:In a cross-sectional study of 318 patients with chronic systolic HF recruited in 48 German primary care practices, we evaluated the patient-reported European HF Self-care Behaviour scale (EHFScBs) assessments (range 12?60, where lower scores indicate better self-care). Potential determinants included socio-demographic (e.g. age, living status), clinical (e.g. NYHA class, LVEF, NT-proBNP levels, co-morbidities), behavioural (e.g. smoking and alcohol intake), psychosocial (SF-36 scales and KCCQ domains, e.g. quality of life and self-efficacy) and depression status (PHQ-D), plus previous health care utilisation. Mixed regression modelling was applied.Results:Patients had a mean (SD) age of 69.0 (10.4) years and were 71% male. They had a good overall EHFScBs score of 24.7 (7.8) (n=274). In the final regression model (n=271), six determinants were retained (?; descriptive p-value): self-efficacy (-0.24; <.001), age (-0.22; <.001), prosthetic heart valve (-0.14; .01), referrals to cardiologists (-0.14; .02), peripheral arterial disease (0.13; .03) and quality of life (0.16; .02).Conclusion:In this exploratory cross-sectional study, the potential non-modifiable and modifiable risk factors and resources involved in patients? HF self-care were at the individual and organisational level. Self-efficacy and quality of life are potentially modifiable, so these could be targeted for improvement by enhancing patient motivation, HF education and further supporting a collaborative care approach.